2017
DOI: 10.1016/j.ijggc.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Well integrity for CO2 injection from ships: Simulation of the effect of flow and material parameters on thermal stresses

Abstract: Ships have been shown to be the most cost-effective way to transport CO 2 from many sources in the Nordic region to offshore storage sites. Injection from ships introduces new challenges for the integrity of CO 2 injection wells. The low temperature and the intermittency of CO 2 injected from ships give rise to large temperature variations in the well. Such variations may lead to thermal stresses that exceed the limits of the well construction method and materials.In this paper we present a coupled flow and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…It is undoubtedly important to investigate how the economic performance of CCS power stations can be improved by exploiting the flexible capabilities of the capture unit. The techno-economic literature on flexible operation of CCS power plants is, however, generally separate from studies investigating the effect of this flexible operation on the downstream CO 2 transport and storage system (IEAGHG 2016, Jensen et al 2014, Roy et al 2016, Aursand et al 2017. Recently a study by Spitz et al (2018) found that regular bypass operation has the potential to further increase the variability of CO 2 flows in the transport and storage system, particularly at low carbon prices (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is undoubtedly important to investigate how the economic performance of CCS power stations can be improved by exploiting the flexible capabilities of the capture unit. The techno-economic literature on flexible operation of CCS power plants is, however, generally separate from studies investigating the effect of this flexible operation on the downstream CO 2 transport and storage system (IEAGHG 2016, Jensen et al 2014, Roy et al 2016, Aursand et al 2017. Recently a study by Spitz et al (2018) found that regular bypass operation has the potential to further increase the variability of CO 2 flows in the transport and storage system, particularly at low carbon prices (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The reservoir is connected to the center of the bottom cell in the well, and the main well parameters are summarized in Table 2. This is comparable to the setup of Aursand et al, 4 except that we here employ a full near-well reservoir model instead of a simplified downhole boundary condition in the well.…”
Section: Case Descriptionmentioning
confidence: 86%
“…In our previous work, 4 we employed a robust method (see, e.g., Munkejord and Hammer 31 and Munkejord et al 32 ) able to accurately capture the pressure waves inherent in the flow model. Thus, the time-step length of that method was limited by the Courant-Friedrichs-Lewy (CFL) stability criterion based on the speed of sound, that is, giving short time-step sizes.…”
Section: Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4] we considered single-and two-phase flow during blow-out and shut-in in vertical CO2-injection wells. In [1] we studied the heat transfer through the different materials surrounding the vertical pipe, and the resulting thermal stresses. For intermittent injection scenarios for direct offshore ship offloading, we found that high thermal stresses could occur.…”
mentioning
confidence: 99%